Atrial Fibrillation and Ventricular Tachyarrhythmias: Advancements for Better Outcomes - Gheini, Alireza; Pourya, Afsoun; Pooria, Ali (Cardiovascular & Haematological Disorders - Drug Targets, 2020)
Cardiac arrhythmias are associated with several cardiac diseases and are prevalent in people with or without structural and valvular abnormalities. Ventricular arrhythmias (VA) can be life threating and their onset require immediate medical attention. Similarly, atrial fibrillation and flutter lead to stroke, heart failure and even death. Optimal treatment of VA is variable and depends on the medical condition associated with the rhythm disorder (which includes reversible causes such as myocardial ischemia or pro-arrhythmic drugs). While an implanted cardioverter defibrillator is often indicated in secondary prevention of VA. This review highlights the newest advancements in these techniques and management of ventricular and atrial tachyarrhythmias, along with pharmacological therapy.
Keywords: atrial tachyarrhythmias